Clinical endocrinology of companion animals - Rand, Jacquie (Ames, Iowa : Wiley-Blackwell, 2013)
Clinical Endocrinology of Companion Animals offers fast access to clinically relevant information on managing the patient with endocrine disease. Written by leading experts in veterinary endocrinology, each chapter takes the same structure to aid in the rapid retrieval of information, offering information on pathogenesis, signalment, clinical signs, diagnosis, differential diagnosis, treatment, prognosis, and prevention for a broad list of endocrine disorders. Chapters begin with brief summaries for quick reference, then delve into greater detail. With complete coverage of the.
1 Hypoadrenocorticism in dogs -- 2 Hypoadrenocorticism in cats -- 3 Hypoadrenocorticism in other species -- 4 Critical illness-related corticosteroid insufficiency (previously known as relative adrenal insufficiency) -- 5 Hyperadrenocorticism in dogs -- 6 Primary functioning adrenal tumors producing signs similar to hyperadrenocorticism including atypical syndromes in dogs -- 7 Hyperadrenocorticism in cats -- 8 Primary functioning adrenal tumors producing signs similar to hyperadrenocorticism including atypical syndromes in cats -- 9 Hyperadrenocorticism in ferrets -- 10 Hyperadrenocorticism and primary functioning adrenal tumors in other species (excluding horses and ferrets) -- 11 Hyperadrenocorticism (pituitary pars intermedia dysfunction) in horses -- 12 Primary hyperaldosteronism -- 13 Pheochromocytoma in dogs -- 14 Pheochromocytoma in cats -- 15 Canine diabetes mellitus -- 16 Feline diabetes mellitus -- 17 Diabetes mellitus in other species -- 18 Canine diabetic emergencies -- 19 Feline diabetic ketoacidosis -- 20 Equine metabolic syndrome/insulin resistance syndrome in horses -- 21 Insulinoma in dogs -- 22 Insulinoma in cats -- 23 Insulinomas in other species -- 24 Gastrinoma, glucagonoma, and other APUDomas -- 25 Hypothyroidism in dogs -- 26 Hypothyroidism in cats -- 27 Hypothyroidism in other species -- 28 Hyperthyroidism in dogs -- 29 Hyperthyroidism in cats -- 30 Hyperthyroidism/thyroid neoplasia in other species -- 31 Hypocalcemia in dogs -- 32 Hypocalcemia in cats -- 33 Hypocalcemia in other species -- 34 Hypercalcemia in dogs -- 35 Hypercalcemia in cats -- 36 Hypercalcemia in other species -- 37 Nutritional secondary hyperparathyroidism in reptiles -- 38 Hyposomatotropism in dogs -- 39 Hyposomatotropism in cats -- 40 Acromegaly in dogs -- 41 Acromegaly in cats -- 42 Diabetes insipidus and polyuria/polydipsia in dogs -- 43 Diabetes insipidus in cats -- 44 Hyponatremia, SIADH, and renal salt wasting -- 45 Estrogen- and androgen-related disorders -- 46 Progesterone and prolactin-related disorders; adrenal dysfunction and sex hormones -- 47 Pathologic reproductive endocrinology in other species.
Includes bibliographical references and index.
Keywords: Veterinary endocrinology; Pets -- Diseases; Endocrine Glands -- physiopathology; Endocrine System Diseases -- diagnosis; Endocrine System Diseases -- veterinary; Pets; MEDICAL -- Veterinary Medicine -- Food Animal; MEDICAL -- Veterinary Medicine -- Small Animal; Pets -- Diseases; Veterinary endocrinology; Endocrine System Diseases -- veterinary; Endocrine Glands -- physiopathology; Endocrine System Diseases -- diagnosis; Pets; Electronic books